DIGITAL TEACHING MATERIALS OF PRACTICUM ACCOUNTING FOR SERVICE, TRADE AND MANUFACTURING COMPANY FOR SMK MAITREYAWIRA TANJUNGPINANG - Ivone Ivone; Sheila Septiany (Universitas Internasional Batam, 2022)
Online learning has become the main activity in teaching and learning activities during this pandemic. Therefore, schools are increasingly paying attention to the implementation of online learning as well as offline learning. One of the schools that is running online learning is SMK Maitreyawira Tanjungpinang and is used as a partner in this community engagement project. The process of preparing digital materials through the process of interview, observation and consultation with the school. The application of online learning is tailored to the accounting department at SMK Maitreyawira Tanjungpinang which contains the subject theory of Practicum Accounting for Service, Trade, and Manufacturing Company so that they must use digital teaching materials in module, ppt and video and practice questions as learning materials. The preparation of the module is adjusted to the curriculum and competence of school materials. The digital teaching materials that have been compiled have helped the school in making online accounting learning more effective and efficient.